Molecular and morphological detection of Setaria tundra in roe deer (Capreolus capreolus) from Lithuania - Misailove-Riboke, Silvija; Lipatova, Indre; Razanske, Irma; Mazeika, Vytautas; Sakalauskas, Povilas; Kibisa, Arturas; Paulauskas, Algimantas (Folia parasitologica, 2024)
Setaria spp. are vector-borne parasitic roundworms commonly found in the abdominal cavities of wild and domesticated ungulates globally. The objective of this study was to conduct a morphological and molecular analysis of Setaria tundra Issaitshikoff et Rajewskaya, 1928, collected from roe deer Capreolus capreolus Linnaeus in Lithuania. The morphological characteristics of S. tundra described and illustrated. The amplification of the 12S rRNA and 18S rRNA genes confirmed the presence of S. tundra. This is the first case report of S. tundra in roe deer in Lithuania.
Keywords: Deer; vysoká zvěř; RNA ribozomální 18S; Phylogeny; Female; zvířata; Setariasis; Lithuania; setariáza; RNA ribozomální; Litva; ženské pohlaví; Setaria Nematode; Male; fylogeneze; RNA, Ribosomal; Setaria (Nematoda); Animals; RNA, Ribosomal, 18S; mužské pohlaví